2013
DOI: 10.1016/j.wear.2013.01.073
|View full text |Cite
|
Sign up to set email alerts
|

Nano-scratch, nanoindentation and fretting tests of 5–80nm ta-C films on Si(100)

Abstract: Wear and stiction forces limit the reliability of Silicon-based micro-systems when mechanical contact occurs. Ultra-thin filtered cathodic vacuum arc (FCVA) ta-C films are being considered as protective overcoats for Si-based MEMS devices. Fretting, nano-scratch and nanoindentation of different thickness (5, 20 and 80 nm) ta-C films deposited on Si(100) has been performed using spherical indenters to investigate the role of film thickness, tangential loading, contact pressure and deformation mechanism in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…The friction coefficient at yield is commonly reported to be ~0.05-0.1 for carbon films when sliding against spherical diamond probes [9,42]. Differences in elastic deformation and plastic ploughing have a marked influence on the evolution of the friction vs. load in the nano-scratch test.…”
Section: Influence Of Probe Geometry and Deformation On Frictionmentioning
confidence: 99%
See 1 more Smart Citation
“…The friction coefficient at yield is commonly reported to be ~0.05-0.1 for carbon films when sliding against spherical diamond probes [9,42]. Differences in elastic deformation and plastic ploughing have a marked influence on the evolution of the friction vs. load in the nano-scratch test.…”
Section: Influence Of Probe Geometry and Deformation On Frictionmentioning
confidence: 99%
“…The authors of this paper have also performed a more complete characterisation of carbon coatings by combining the results of the nanoindentation tests with additional nanomechanical and nano-tribological test capability, namely nano-scratch, nano-impact and nano-wear [9][10][11]. These tests provided complementary information about the durability of DLC films in these more complex mechanical loading situations.…”
Section: Introductionmentioning
confidence: 99%
“…Recent nanoscratch studies revealed that film thickness had great effect on the critical normal load that induced interfacial failure [67,[74][75][76]. Beake et al [74] characterized the nanoscratch induced surface damages in Ta-C films of different thicknesses deposited on a Si substrate.…”
Section: Top Surface Nanoscratchingmentioning
confidence: 99%
“…Beake et al [74] characterized the nanoscratch induced surface damages in Ta-C films of different thicknesses deposited on a Si substrate. The scratching results shown in Fig.…”
Section: Top Surface Nanoscratchingmentioning
confidence: 99%
“…Beake and co-workers have reported nanomechanical and nanotribological (nano-scratch and nano-wear) characterisation of a wide range of thin films on Si, with thicknesses from 5 nm (ta-C) to 1500 nm (TiN) performing nanoindentation with Berkovich indenters combined with nano-scratch testing with spherical indenters [49,[54][55][56][57]. A key motivation for studying several of these was to understand the interplay between film thickness and interfacial toughness for MEMS and protective thin film applications.…”
Section: Influence Of Film Stress and Thicknessmentioning
confidence: 99%